2018
DOI: 10.1001/jamanetworkopen.2018.1281
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mortality and Acute Aortic Events With Ascending Aortic Aneurysm

Abstract: Key Points Question What are the growth rate and risk of complications in patients with moderately dilated ascending aortas? Findings This systematic review and meta-analysis of 20 studies including 8800 patients found that the ascending aorta growth rate was 0.61 mm/y, and the incidence of elective aortic surgery was 13.82%. The linearized mortality rate was 1.99% per patient-year, while the rate of aortic dissection, aortic rupture, and mortality was 2.16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
52
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 37 publications
0
52
1
1
Order By: Relevance
“…Thoracic aortic aneurysm (TAA) and abdominal aortic aneurysm (AAA) are major vascular diseases induced by systemic atherosclerosis. TAA and AAA are related to increased morbidity and mortality rates, especially due to the rupture of TAA/AAA (1,2). Since the mortality of TAA/ AAA rupture is still very high, open surgery or endovascular aortic repair should be performed before rupture occurs (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thoracic aortic aneurysm (TAA) and abdominal aortic aneurysm (AAA) are major vascular diseases induced by systemic atherosclerosis. TAA and AAA are related to increased morbidity and mortality rates, especially due to the rupture of TAA/AAA (1,2). Since the mortality of TAA/ AAA rupture is still very high, open surgery or endovascular aortic repair should be performed before rupture occurs (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…TAA and AAA are related to increased morbidity and mortality rates, especially due to the rupture of TAA/AAA (1,2). Since the mortality of TAA/ AAA rupture is still very high, open surgery or endovascular aortic repair should be performed before rupture occurs (2)(3)(4). Furthermore, patients with TAA/AAA often have coronary artery disease (CAD), which results in an even greater mortality rate (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have found that many patients with acute ascending aortic dissection have aortic diameters of <5.5 cm at hospital presentation [ 14 , 15 ]. Moreover, Ming et al conducted a systematic review and meta-analysis about the natural history of ascending aortic aneurysm and found the conclusions about the conventional risk factors, such as aortic diameters, not only varied significantly but were often contradictory among studies [ 16 ]. For example, 4 studies [ 17 20 ] identified that aortic dilation had no association with baseline aortic diameter, while 2 studies [ 21 , 22 ] reported higher annual aortic growth rate with lower baseline aortic diameter.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, however, long-term independent studies [12][13][14] produced evidences supporting new guidelines providing separate threshold for aortic surgery in MF and BAV patients [12][13][14]. Indeed, a recent meta-analysis [15] indicates a low risk of rupture or dissection of moderately dilated aortas without evidence that those related to BAV perform more poorly than others. These data further support the recommended threshold of 55 mm for intervention in BAVs without risk factors [12][13][14].…”
Section: Introductionmentioning
confidence: 99%